Analysis of Combustion Temperature on the Use of B100 and B20 Fuels that Operate in the Long Term - W Saputro; J Sentanuhady; L Edahwati; A K Faizin (BIOMEJ, 2022)
Indonesian people's reliance on diesel fuel is still quite strong, as seen by the rising yearly use of diesel. Because diesel is a fossil fuel that is not renewable, rising diesel usage is a concern that must be anticipated. One approach to deal with this is to switch from fossil fuels to biofuels like biodiesel. Because Indonesia is the world's largest producer of palm oil, biodiesel from palm oil is an alternative. Although biodiesel may potentially be used directly in diesel engines, there are few researches on the impacts of utilizing it and the possibility for further development. As a result, the goal of this research is to look at the combustion temperature of B100 and B20 fuels in long-term testing. Two Kubota diesel engines with 376 cc cylinder volumes are used in this investigation. Each engine will be connected to a generator that will provide 4000 W of electricity to the halogen bulbs. The two engines will run on separate fuels, with the first using B20 and the second on B100 from palm oil. The engine has a continuous rotational speed of 2200 rpm and has been running for 300 hours without stopping. The combustion temperature of the cylinder head, cylinder block, and exhaust gas pipe is measured every multiple of 4 hours. With 1.7 percent, 1.2 percent, and 2.7 percent, respectively, the B100 engine delivers lower combustion temperatures in the cylinder head, cylinder block, and pipe exhaust gas.